1998
DOI: 10.1191/026921598668275996
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin type A and short-term electrical stimulation in the treatment of upper limb flexor spasticity after stroke: a randomized, double-blind, placebo-controlled trial

Abstract: The placebo-controlled trial favours the concept that electrical stimulation enhances the effectiveness of BtxA in the treatment of chronic upper limb flexor spasticity after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
140
1
9

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 216 publications
(152 citation statements)
references
References 12 publications
2
140
1
9
Order By: Relevance
“…23,24,26,28,29 Baseline spasticity was of comparable severity in the BoNT and placebo groups in seven trials, 11,21,23,24,26,27,29 whereas information on baseline clinical characteristics was considered insufficient in the other four studies. 7,10,25,28 Considering the potential relevance of concomitant drug treatments, rehabilitation, or devices, this information was not reported in seven trials, 7,11,21,24,[27][28][29] whereas one study indicated that no patient received concomitant therapy 23 and three studies reported no between-group differences. 10,25,26 In two studies, 23,29 all patients received a concomitant rehabilitation program.…”
Section: Findings Description Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…23,24,26,28,29 Baseline spasticity was of comparable severity in the BoNT and placebo groups in seven trials, 11,21,23,24,26,27,29 whereas information on baseline clinical characteristics was considered insufficient in the other four studies. 7,10,25,28 Considering the potential relevance of concomitant drug treatments, rehabilitation, or devices, this information was not reported in seven trials, 7,11,21,24,[27][28][29] whereas one study indicated that no patient received concomitant therapy 23 and three studies reported no between-group differences. 10,25,26 In two studies, 23,29 all patients received a concomitant rehabilitation program.…”
Section: Findings Description Of Studiesmentioning
confidence: 99%
“…7,10,25,28 Considering the potential relevance of concomitant drug treatments, rehabilitation, or devices, this information was not reported in seven trials, 7,11,21,24,[27][28][29] whereas one study indicated that no patient received concomitant therapy 23 and three studies reported no between-group differences. 10,25,26 In two studies, 23,29 all patients received a concomitant rehabilitation program. Information on clinical side effects and adverse events was reported in all trials, but severe adverse effects were a priori defined in one study only.…”
Section: Findings Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations